Using of geogebra software to improve understanding of vector and kinematic concepts in online physics course - Jeffry Handhika*; Mislan Sasono (UNIVERISTAS PGRI MADIUN, 2021)
This research aims to improve understanding of vector and kinematics concepts with Geogebra software in online learning (online using e-Learning UNIPMA (e-LMA). The method used in this research is a descriptive conducted on four students who took fundamental physics for the 2019/2020 academic year. The research steps are described as follows 1) creating a profile and analyzing understanding of vector concepts and kinematics before implementing e-LMA, (2) describing the learning process through e-LMA, (3) creating a profile, and analyze students' understanding of vector concepts and kinematics after the implementation of e-LMA. E-LMA-assisted learning by integrating materials and assignments with GeoGebra software can improve understanding of vector and kinematic concepts